2022
DOI: 10.1186/s41065-021-00215-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel four-gene diagnostic signature for patients with sepsis by integrating weighted gene co-expression network analysis and support vector machine algorithm

Abstract: Sepsis is a life-threatening condition in which the immune response is directed towards the host tissues, causing organ failure. Since sepsis does not present with specific symptoms, its diagnosis is often delayed. The lack of diagnostic accuracy results in a non-specific diagnosis, and to date, a standard diagnostic test to detect sepsis in patients remains lacking. Therefore, it is vital to identify sepsis-related diagnostic genes. This study aimed to conduct an integrated analysis to assess the immune score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…LCK mainly participates in T cell signal transduction and is one of the therapeutic targets for many inflammation-mediated pathological processes [37]. Several studies have demonstrated that LCK is a crucial gene in sepsis patients [38][39][40]. The F13A1 gene encodes coagulation factor XIII A, and F13A1 gene mutations may lead to abnormal coagulation factor XIII function, resulting in coagulation system diseases [41].…”
Section: Discussionmentioning
confidence: 99%
“…LCK mainly participates in T cell signal transduction and is one of the therapeutic targets for many inflammation-mediated pathological processes [37]. Several studies have demonstrated that LCK is a crucial gene in sepsis patients [38][39][40]. The F13A1 gene encodes coagulation factor XIII A, and F13A1 gene mutations may lead to abnormal coagulation factor XIII function, resulting in coagulation system diseases [41].…”
Section: Discussionmentioning
confidence: 99%
“…CCL5 is a chemokine gene clustered on the chromosome 17, which is a potential target for sepsis [ 31 ]. Li M identified a gene signature, containing the hub genes CCL5, and established a model that could be used to diagnose patients with sepsis [ 32 ]. The protein encoded by CCR7 is a member of the G protein coupled receptor family.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al also analyzed an adult ICU dataset (5) using WGCNA methodology to highlight significant gene modules in sepsis (6). Also, Li et al used WCGNA to demonstrate inflammation-related genes and to identify transcriptomic markers (7). Furthermore, in this study, WGCNA was integrated with the support vector machine (SVM) algorithm.…”
mentioning
confidence: 99%